"Land Reform Costly": Zimbabwe Land Reform Negation Discourse in the Print Media. Issue 1 (2nd January 2019) - Jakaza, Ernest
Abstract: The Zimbabwean land reform programme's inception and impact have been studied from various disciplinary perspectives chronicling and profiling its negatives and positives. However, very few discourse-linguistic studies have been carried out on this topic, even though the media is evaluative in its reporting of relevant news. The media's digestion and subjectivity in news reporting is well documented, making objectivity in news reporting a "myth." The dichotomisation of news reporting is evident in state and private newspapers. This study is an appraisal and controversy analysis of negation and affirmation discourse realised in private and state print media in Zimbabwe. Though it is known that the private media is a mouthpiece of opposition political parties, evaluations of negation discourse on the Zimbabwean land reform programme have not been carried out. The study appraises the use of negation discourse in the Zimbabwean independent print media and questions whether the media's projections are controversial and/or myths.